Neurological Gait Abnormalities Moderate the Functional Brain Signature of the Posture First Hypothesis - Holtzer, Roee (Brain Topogr, 2015)
The posture first hypothesis suggests that under dual-task walking conditions older adults prioritize gait over cognitive task performance. Functional neural confirmation of this hypothesis, however, is lacking. Herein, we determined the functional neural correlates of the posture first hypothesis and hypothesized that the presence of neurological gait abnormalities (NGA) would moderate associations between brain activations, gait and cognitive performance. Using functional near-infrared spectroscopy we assessed changes in oxygenated hemoglobin levels in the pre-frontal cortex (PFC) during normal walk and walk while talk (WWT) conditions in a large cohort of non-demented older adults (n = 236; age = 75.5 ± 6.49 years; female = 51.7 %). NGA were defined as central (due to brain diseases) or peripheral (neuropathic gait) following a standardized neurological examination protocol. Double dissociations between brain activations and behavior emerged as a function of NGA. Higher oxygenation levels during WWT were related to better cognitive performance (estimate = 0.145; p < 0.001) but slower gait velocity (estimate = −6.336, p <0.05) among normals. In contrast, higher oxygenation levels during WWT among individuals with peripheral NGA were associated with worse cognitive performance (estimate = −0.355; p <0.001) but faster gait velocity (estimate = 14.855; p <0.05). Increased activation in the PFC during locomotion may have a compensatory function that is designed to support gait among individuals with peripheral NGA.